EFFECT OF PLANT GROWTH REGULATORS ON IN VITRO PROPAGATION OF TAGETES ERECTA - BANANI DEKA,; ANANIA ARJUNA, (International Journal of Pharma and Bio Sciences, 2014)
Tagetes erecta is a plant of great medicinal value and is in high commercial demand due to its various uses in religious purposes, as eatables, and is used for the treatment of headache and strengthening of the heart, treating wounds and prevent them from getting infected with bacteria and toxins. Young tender leaves of T.erecta were collected from plants grown in pots under adequate sunlight and rainfall.. Leaves were sterilised with 70% ethanol for 5 minutes and 0.02% Mercuric chloride for 3 minutes and inoculated in MS medium supplemented with Kn, IAA, NAA and 2,4-D in different combinations (0, 0.5, 2.5, 5.0, 10 mg/L). 50% callus formation are observed in 0.5 mg/L Kn from LT, 0.5 mg/L Kn + 2.5 mg/L IAA from LM, 0.5 mg/L Kn + 10.0 mg/L IAA from LM, 2.5 mg/L Kn + 0.5 mg/L IAA from LT, 5.0 mg/L Kn + 2.5 mg/L 2,4-D from LT and 10.0 mg/L Kn + 0.5 mg/L IAA from LM. 100% callus formation occurred in the combinations of 0.5 mg/L Kn + 5.0 mg/L 2,4-D from LB and LM, 2.5 mg/L Kn from LT and 5.0 mg/L Kn + 0.5 mg/L IAA from LT. Root formation was observed in the concentration of 2.5 mg/L Kn + 0.5 mg/L IAA from LT. Root formation was observed in low concentration of Kn in combination with a low concentration of cytokinin. Callus induction resulted in high concentration of Kn and cytokinin.. It has also been observed that the explants responded differently towards different growth regulators in varying concentrations. The best callus growth was found using the Kn and IAA as growth regulators within a short time period.